Dramaturgies of documentary objects (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This text shares different ways of making dramaturgies with documentary objects as part of processes of the theater of documentary objects: ethnographic notebooks, feedback dramaturgies, translation of field research into visual dramaturgies, space as dramaturgy, etc. The practices mentioned as examples come from the author's experience as an “object detective” with her groups Oligor y Microscopía and Agencia El Solar in Mexico and Spain.
Keywords: dramaturgy; material culture; memory studies; theatre of documentary objects